The Affect of Host Plant on Aphid Population Growth - Dostal, Elyse; Enders, Laramy; Smith, C. Michael (My University, 2017)
Damage from aphids to wheat plants is noticeable from a distance and can result in water stress, reduced plant growth and wilting. Different aphids are said to cause different colorations when damaging the plants. The comparison of aphid performance on a set of closely related species can help identify traits related to plant defense and aphid performance. Such studies can help inform future experiments that study specific mechanisms of plant resistance. Its important to know what causes aphids to damage some plants more than others so we can find ways to prevent it. I observed the effects that wheat, barley and sorghum have on the population growth rate of corn leaf aphids and green bugs. Also, the effect the aphids have on the plants and how much they damage each type. Will one aphid species have an exceptionally higher rate of reproduction on a specific plant? Is aphid population growth affected by competition between species? I found the green bug population grew faster than the corn leaf aphids and they preferred the wheat, which in return resulted in the wheat having the highest plant damage.
Citation: Dostal, E. (2017). The Affect of Host Plant on Aphid Population Growth . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.